PENGARUH STATUS CONSUMPTION, FASHION INNOVATIVENESS, BRAND CONSCIOUSNESS, PRICE CONSCIOUSNESS, DAN QUALITY CONSCIOUSNESS TERHADAP HEDONIC CONSUMPTION (Studi pada Pembeli dan Pengguna Fashion Streetwear di Kota Jakarta) - Amirah Azhaar Cahyani; Wilopo Wilopo; Rizal Alfisyahr (Fakultas Ilmu Administrasi Universitas Brawijaya, 2019)
Type of research is explanatory research. The sample used in this research were 116 respondents who are buyer and user of fashion streetwear in Jakarta. The sampling technique used purposive sampling technique. Methods of data collecting by questionnaire. Data analysis using descriptive analysis and multiple linear regression. The result showed that: (1) there is significant influence partially of status consumption (X1) to hedonic consumption (Y), fashion innovativeness (X2) to hedonic consumption (Y), brand consciousness (X3) to hedonic consumption (Y), price consciousness (X4) to hedonic consumption (Y), quality consciousness (X5) to hedonic consumption (Y). (2) there is significant influence simultaneously perception of status consumption (X1), fashion innovativeness (X2), brand consciousness (X3), price consciousness (X4), quality consciousness (X5) of hedonic consumption (Y). It is recommended that company specially in fashion industry able to maintain brand image because brand consciousness variable has a dominant influence on hedonic consumption, and improve the quality of the products because the quality of the products is an important for consumer which has hedonic consumption motive so they can keep interested and more loyal towards product in fashion industry. Kеywords: Streetwear Fashion, Status Consumption, Fashion Innovativeness, Brand Consciousness, Price Consciousness, Quality Consciousness, Hedonic Consumption. АBSTRАK Jenis penelitian yang digunakan pada penelitian ini adalan penelitian penjelasan (explanatory research). Sampel yang digunakan pada penelitian ini sebanyak 116 orang responden yang membeli dan menggunakan produk Fashion Streetwear di Kota Jakarta. Teknik yang digunakan dalam penelitian ini adalah teknik purposive sampling. Metode pengumpulan data dengan kuesioner. Analisis data yaitu analisis deskriptif dan analisis regresi linier berganda. Hasil penelitian ini menunjukkan bahwa: (1) terdapat pengaruh signifikan secara parsial antara Status Consumption (X1) terhadap Hedonic Consumption (Y). Fashion Innovativeness (X2) terhadap Hedonic Consumption (Y). Brand Consciousness (X3) terhadap Hedonic Consumption (Y). Price Consciousness (X4) terhadap Hedonic Consumption (Y). Quality Consciousness(X5) terhadap Hedonic Consumption (Y). (2) terdapat pengaruh signifikan secara bersama-sama Status Consumption (X1), Fashion Innovativeness (X2), Brand Consciousness (X3), Price Consciousness (X4), dan Quality Consciousness (X5), secara bersama-sama berpengaruh terhadap Hedonic Consumption (Y). Disarankan agar pihak perusahaan terutama pada bidang industri fashion dapat mempertahankan citra merek karena variabel Brand Consciousness mempunyai pengaruh yang dominan dalam mempengaruhi Hedonic Consumption., dan terus meningkatkan kualitas suatu produk karena kualitas produk merupakan hal yang sangat penting agar para konsumen yang memiliki motif belanja hedonic akan terus tertarik dan lebih loyal kepada produk dari industri fashion. Kаtа Kunci: Fashion Streetwear, Status Consumption, Fashion Innovativeness, Brand Consciousness, Price Consciousness, Quality Consciousness, Hedonic Consumption.